Neural responses to instructed positive couple interaction: an fMRI study on compliment sharing - Eckstein, Monika; Stößel, Gabriela; Gerchen, Martin Fungisai; Bilek, Edda; Kirsch, Peter; Ditzen, Beate (Social cognitive and affective neuroscience, 2023)
Love is probably the most fascinating feeling that a person ever experiences. However, little is known about what is happening in the brains of a romantic couple—the central and most salient relationship during adult age—while they are particularly tender and exchanging loving words with one another. To gain insight into nearly natural couple interaction, we collected data from N = 84 individuals (including N = 43 heterosexual couples) simultaneously in two functional magnetic resonance imaging scanners, while they sent and received compliments, i.e. short messages about what they liked about each other and their relationship. Activation patterns during compliment sharing in the individuals revealed a broad pattern of activated brain areas known to be involved in empathy and reward processing. Notably, the ventral striatum, including parts of the putamen, was activated particularly when selecting messages for the partner. This provides initial evidence that giving a verbal treat to a romantic partner seems to involve neural reward circuitry in the basal ganglia. These results can have important implications for the neurobiological mechanisms protecting and stabilizing romantic relationships, which build a highly relevant aspect of human life and health.